Self-aggregation of oxidized procyanidins contributes to the formation of heat-reversible haze in apple-based liqueur wine. (15th March 2019) - Millet, Melanie; Poupard, Pascal; Guilois-Dubois, Sophie; Zanchi, Drazen; Guyot, Sylvain
Highlights: Oxidation of apple procyanidins in model solutions induced haze formation. An increase in the degree of polymerization of procyanidins accelerated haze formation. Intramolecular coupling induced by oxidation was involved in haze formation. Haze formed in a model solution was partially reversible and was similar to pommeau haze. Abstract: The ability of tannins to self-associate or form complexes with other macromolecules has important nutritional implications but can also result in defects in beverages. In addition, oxidation may be involved in the aggregation properties of tannins. In order to assess the impact of tannin oxidation on their self-association, oligomeric procyanidins were oxidized in a model solution and their aggregation kinetics were studied using light scattering. Under the conditions tested, only oxidized procyanidins were involved in haze formation. An increase in the level of oxidation and the degree of polymerization of procyanidins enhanced aggregation. Procyanidin oxidation products were depolymerized and the evolution of their markers was monitored throughout the aggregation process using liquid chromatography coupled with mass spectrometry. This revealed the involvement of intramolecular coupling in reversible haze formation. The haze formed in a model solution was partially reversible at high temperature. This property was similar in pommeau, an apple-based beverage. This work highlighted the involvement of oxidized tannins in reversible haze.